Comparison of plate and compression screw in the treatment of hallux rigidus with arthrodesis: a retrospective study - Yurteri, Ahmet; Mercan, Numan; Yıldırım, Ahmet (The European Research Journal, 2024)
Objectives: Although numerous surgical techniques and fixation methods have been described for the treatment of hallux rigidus (HR) with arthrodesis, consensus on the gold standard treatment has not been reached. The aim of this study is to retrospectively compare the clinical and radiological outcomes of compression screw fixation and plate fixation in the treatment of HR with arthrodesis. Methods: Patients who underwent arthrodesis surgery due to HR between January 2021 and December 2023 at a single center were retrospectively reviewed. Patients who met the inclusion criteria were divided into two groups: those who underwent arthrodesis with plate fixation (PLATE) and those who underwent arthrodesis with compression screw fixation (SCREW). Demographic data including age, gender, affected side, operative time, hallux valgus angle (HVA), dorsiflexion angle, AOFAS scores, and implant irritation data were compared among patients with at least 3 months of follow-up. Results: It was observed that all patients included in the study had successful bone union without any complications. There were no significant differences between the two groups in terms of age, gender, affected side, preoperative HVA, and preoperative AOFAS scores (P=0.970, P=0.426, P=0.694, P=0.216, and P=0.905, respectively). The mean operation time and postoperative AOFAS score were lower in the PLATE group compared to the SCREW group (P=0.006 and P=0.004, respectively). However, in the SCREW group, the dorsiflexion angle and the rate of implant irritation were lower compared to the PLATE group (P=0.016 and P=0.01, respectively). Conclusions: In the surgical treatment of HR, both plate fixation arthrodesis and compression screw arthrodesis are reliable surgical techniques. While plate fixation arthrodesis is a faster and more practical method, arthrodesis with a compression screw results in fewer complaints related to the implant and provides a more functional recovery.